Financial Policies and Requirements of Economic Reform In Iraq - Nadia khutheir Ganawi, Suad Jawad Kadhim, Amel Asmar Zaboon, (Opción, 2019)
This paper endeavors to investigate the effect of approach changes on financial improvement and Economic development in Iraq from 1980 to 2015. In view of the Augmented Dickey Fuller test and exogenous break test, we look at the effect of arrangement changes. The results show that all factors aside from local credit are non-stationary at the dimension. Local credit given by banks experienced negative development, and it diminished in pace after policy changes, which suggests that the job of government declined after the progression. Notwithstanding, there is no effect of strategy changes on some of the economic development variables.